2018
DOI: 10.3892/etm.2018.6479
|View full text |Cite
|
Sign up to set email alerts
|

Screening of genes associated with inflammatory responses in the endolymphatic sac reveals underlying mechanisms for autoimmune inner ear diseases

Abstract: The current study analyzed gene expression profiles of the endolymphatic sac (ES) in rats and identified expressed genes, present in the human and rat ES, to reveal key hubs for inflammatory responses. Microarray data (accession no. E-MEXP-3022) were obtained from the European Bioinformatics Institute database, including three biological replicates of ES plus dura tissues and three replicates of pure dura tissues form rats. Differentially expressed genes (DEGs) were screened using the Linear Model for Microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…CCL21 and CCL19 are genes encoding the pro-inflammatory chemokine ligands that play an essential role in recruiting normal lymphocyte or activated T cells from the peripheral blood to the local injured area in traumatic and acute noise stresses. 28 IL25 is a pro-inflammatory cytokine favoring the Th2-type immune response. 29 SAA1 is a major acute-phase protein that is triggered by an inflammation response associated with the stimulation of cytokine/chemokine, including IL8, IL6, CXCL5, and CCL2 production and knockdown of SAA1 , resulting in a significant reduction of the pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 and CCL19 are genes encoding the pro-inflammatory chemokine ligands that play an essential role in recruiting normal lymphocyte or activated T cells from the peripheral blood to the local injured area in traumatic and acute noise stresses. 28 IL25 is a pro-inflammatory cytokine favoring the Th2-type immune response. 29 SAA1 is a major acute-phase protein that is triggered by an inflammation response associated with the stimulation of cytokine/chemokine, including IL8, IL6, CXCL5, and CCL2 production and knockdown of SAA1 , resulting in a significant reduction of the pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…ITGA1 was also reported to be closely associated with diabetes and diabetic retinopathy [ 34 , 36 ]. A previous study has revealed that abnormal expression of ITGA1, which was an inflammatory-associated gene, may be associated with the development of autoimmune inner ear disease [ 37 ]. In this study, ITGA1 was found to be significantly upregulated in the noise-stimulated mice cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high expression of MYL9/12 was related to sepsis-induced acute kidney injury, inflamed mouse airways, and patients with eosinophilic chronic rhinosinusitis (Wu et al, 2015;Hayashizaki et al, 2016). Similarly, Zhang et al (2018) identified ITGA1 as an inflammatory-associated gene. Notably, we speculate that the high SFB population may be driving the predicted ileal mucosa proinflammatory status found in broilers early exposed to L. Nevertheless, the mechanism underlying SFB-mediated inflammation is yet unknown and must be further explored.…”
Section: Discussionmentioning
confidence: 99%